Dissection of the methyl-CpG binding domain from the chromosomal protein MeCP2 - Xinsheng Nan; Richard R. Meehan; Adrian Bird (1993)
Journal Article Dissection of the methyl-CpG binding domain from the chromosomal protein MeCP2 Get access Xinsheng Nan, Xinsheng Nan Institute of Cell and Molecular Biology, University of EdinburghKings Buildings, Mayfield Road, Edinburgh EH9 3JR, UK Search for other works by this author on: Oxford Academic PubMed Google Scholar Richard R. Meehan, Richard R. Meehan Institute of Cell and Molecular Biology, University of EdinburghKings Buildings, Mayfield Road, Edinburgh EH9 3JR, UK Search for other works by this author on: Oxford Academic PubMed Google Scholar Adrian Bird Adrian Bird * Institute of Cell and Molecular Biology, University of EdinburghKings Buildings, Mayfield Road, Edinburgh EH9 3JR, UK * To whom correspondence should be addressed Search for other works by this author on: Oxford Academic PubMed Google Scholar Nucleic Acids Research, Volume 21, Issue 21, 25 October 1993, Pages 4886–4892, https://doi.org/10.1093/nar/21.21.4886 Published: 25 October 1993 Article history Received: 05 August 1993 Revision received: 09 September 1993 Accepted: 09 September 1993 Published: 25 October 1993